The Bored Cossack: The Way of a Ukrainian Warrior - Toichkin, Denys (Faces of War, 2025)
The article examines Ukrainian folk paintings of Cossack Mamai as the most complete visual archetype of the Cossack, a professional warrior of the Early Modern period. It argues that Mamai’s static posture and melancholic expression should not be interpreted solely as reflection or sadness, but primarily as a state of boredom, understood in the philosophical sense developed by Martin Heidegger. This boredom emerges from the Cossack’s relationship with time, the steppe landscape, and a psychotype shaped by warfare, isolation, and environmental monotony. An iconographic analysis of key elements (the tree, horse, weapons, bandura, and utensils) shows Mamai as a wealthy, mobile warrior immobilised by enforced rest. The figure is interpreted as one of existential suspension: bored, waiting, aware of purpose yet unable to realise it. In this reading, Mamai becomes a symbol of Ukrainian mentality and of a long-term historical search for identity and meaning.